Effect of extruded soya seed on reversion of fat and protein percentage and fatty acid composition of goat milk - Schmidely P.; Morand-Fehr P.; Tessier J.; Rouzeau A. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
Extruded soya seed was offered at 0, 10 or 20 percent dry matter (DM) in the diets of mid-lactating goats to assess their effect on the reversion of milk fat and protein contents that occurs in high concentrate diets, and to manipulate milk fatty acid composition. Feeding extruded soya seed increased raw milk yield and milk fat content compared to goats fed the control diet. There was no change in milk protein content. Feeding extruded soya seed reduced the ratio of saturated/monounsaturated fatty acids, and increased linoleic and linolenic acid proportions in milk fat. Incorporation of extruded soya seed in high concentrate diets prevented the reversion of the ratio of milk fat content (MFC) and milk protein content (MPC) in mid lactating goats, and it increased the nutritional value of MFC.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)